Three novel antioxidant peptides isolated from C-phycocyanin against H2O2-induced oxidative stress in zebrafish via Nrf2 signaling pathway - Xu, Fenghua; Zhang, Yun; Qiu, Yuezi; Yang, Fanghao; Liu, Guoxiang; Dong, Xiaolei; Chen, Guang; Cao, Can; Zhang, Qian; Zhang, Shanshan; Li, Bing (Frontiers in Marine Science, 2022)
Background C-phycocyanin (C-PC), a phycobiliprotein from Spirulina platensis, has been confirmed to be an effective antioxidant. Duing to the large molecular weight protein, C-PC is hardly absorbed in the human gut and easy coagulates into lumps. In light of this, highly pure, easy absorption, and small molecular weight polypeptides has won the attention in the recent past. However, there are few studies on the C-PC bioactive peptides. Thus, the objective of this study was find natural multifunctional antioxidant peptides from C-PC and demonstrate their mechanisms. Method In this study, novel antioxidant peptides from pancreatin hydrolysate of C-PC were isolated and purified by using a multi-bioassay-guided method. The DPPH and ABTS radical scavenging in vitro and antioxidant zebrafish model in vivo were used to evaluate the antioxidant activities. Furthermore, the underlying molecular mechanisms of these peptides were investigated by measuring the level of ROS, MDA, SOD, CAT and gene expression in Nrf2 signaling pathway. Results Total three novel active peptides, MHLWAAK (Met-His-Leu-Trp-Ala-Ala-Lys), MAQAAEYYR (Met-Ala-Gln-Ala-Ala-Glu-Tyr-Tyr-Arg), and MDYYFEER (Met-ASP-Tyr-Tyr-Phe-Glu-Glu-Arg) were isolated and purified from pancreatin hydrolysate of C-PC. These synthesized peptides displayed high DPPH and ABTS radical scavenging ability. In addition, in a zebrafish model, the three peptides significantly protected zebrafish embryos from H2O2-induced oxidative injury without toxicity by inhibiting ROS generation, preventing MDA formation, and upregulating the activities of SOD and CAT. Further experiments showed that these peptides could significantly regulated oxidative stress via activating the Nrf2 signaling pathway. Conclusion This study indicates that the antioxidant peptides from C-PC could serve as powerful antioxidants for preventing and treating various diseases associated with oxidative stress.